Collocations in Corpus‐Based Language Learning Research: Identifying, Comparing, and Interpreting the Evidence. (20th February 2017) - Gablasova, Dana; Brezina, Vaclav; McEnery, Tony
Abstract : This article focuses on the use of collocations in language learning research (LLR). Collocations, as units of formulaic language, are becoming prominent in our understanding of language learning and use; however, while the number of corpus‐based LLR studies of collocations is growing, there is still a need for a deeper understanding of factors that play a role in establishing that two words in a corpus can be considered to be collocates. In this article we critically review both the application of measures used to identify collocability between words and the nature of the relationship between two collocates. Particular attention is paid to the comparison of collocability across different corpora representing different genres, registers, or modalities. Several issues involved in the interpretation of collocational patterns in the production of first language and second language users are also considered. Reflecting on the current practices in the field, further directions for collocation research are proposed.